Mechanical, thermal and morphological properties of modified Sabah montmorillonite filled polypropylene nanocomposites - Muthmirah Ibrahim, 1984-; Mat Uzir Wahit, supervisor; Azman Hassan, supervisor; Fakulti Kejuruteraan Kimia (2011)
Thesis (Sarjana Kejuruteraan (Polimer)) - Universiti Teknologi Malaysia, 2011